Answer to Question #215066 in Differential Equations for Prince

Question #215066

(x^2 - 1)dy - (y^2 - 1)dx


1
Expert's answer
2021-07-09T12:53:02-0400

Solving the equation

"(x^2 - 1)dy - (y^2 - 1)dx=0"

We can rewrite as:


"(x^2-1)dy=(y^2-1)dx"

Dividing by "(x^2-1)(y^2-1)" through:


"\\frac{d y}{y^2-1}=\\frac{dx}{x^2-1}"

Integrate both sides :


"\\int \\frac{1}{y^2-1} d y=\\int \\frac{1}{x^2-1} dx"

Evaluate the integrals:


"\\frac{1}{2} \\log (-y+1)-\\frac{1}{2} \\log (y+1)=\n\\frac{1}{2} \\log (-x+1)-\\frac{1}{2} \\log (x+1)+c_{1}"

where "c_{1}" is an arbitrary constant.


Solving for y=y(x) we have


"y=-\\frac{x+e^{2 c_{1}}(x-1)+1}{-x+e^{2 c_{1}}(x-1)-1}"

Simplifying the arbitrary constant, we have


"y=-\\frac{x+c_{1}(x-1)+1}{-x+c_{1}(x-1)-1}"

which is the required solution to the given differential equation.


Need a fast expert's response?

Submit order

and get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

Comments

No comments. Be the first!

Leave a comment

LATEST TUTORIALS
New on Blog